Permeable borders : history, theory, policy, and practice in the United States - Otto, Paul Andrew; Berthier-Foglar, Susanne, 1953- (Berghahn, 2020)
"If the frontier, in all its boundless possibility, was a central organizing metaphor for much of U.S. history, today it is arguably the border that best encapsulates the American experience, as xenophobia, economic inequality, and resurgent nationalism continue to fuel conditions of division and limitation. This boldly interdisciplinary volume explores the ways that historical and contemporary actors in the U.S. have crossed such borders--whether national, cultural, ethnic, racial, or conceptual. Together, these essays suggest new ways to understand borders while encouraging connection and exchange, even as social and political forces continue to try to draw lines around and between people"--